Protease inhibitors from marine sponge and sponge-associated microorganisms - Hong, Tran Thi; Dat, Ton That Huu; Cuong, Pham Viet; Cuc, Nguyen Thi Kim (Vietnam Journal of Science and Technology, 2018)
Protease inhibitors (PIs) are proteins or peptides inhibiting the activity of protease and constitute a very important mechanism for regulating protease activity. So far, PIs have been used for the study of enzyme structures and reaction mechanisms, but recently they have been used in pharmaceutical, agricultural and industrial fields. Compared to terrestrial counterparts, marine environment possesses their unique characters, therefore, they are capable of producing a wide range of novel bioactive compounds including protease inhibitors. In our review, a brief overview of protease inhibitors (e.g., classification, mechanisms, and characteristics of PIs) and protease inhibitors from marine sponges and sponge-associated microorganisms has been reviewed.